Nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material as well as preparation method and application thereof

By precipitating nitrogen-doped graphene quantum dots on sodium bismuthate, the construction of nitrogen-doped graphene quantum dots/sodium bismuthate photocatalytic composite materials, the problem of low activity of existing photocatalysts under visible light is solved, and a higher level of activity is achieved photocatalytic activity and toxic organic compounds degradation efficiency.

CN119406440AActive Publication Date: 2025-02-11HUNAN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411552999.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing photocatalysts such as TiO2 cannot effectively utilize visible light due to their wide band gap, resulting in low absorption efficiency of sunlight. Bismuth-based oxides such as NaBiO3 have problems such as fast electron/hole pair recombination, poor charge mobility and insufficient utilization of reactants. , limits its photoactivity.

Method used

By precipitating nitrogen-doped graphene quantum dots (N-GQDs) on flaky sodium bismuthate, a nitrogen-doped graphene quantum dots/sodium bismuthate photocatalytic composite is constructed, and electron transfer/storage of N-GQDs is utilized. Ability to accelerate interfacial charge carrier migration, extend charge lifetime and improve photocatalytic activity.

Benefits of technology

The activity of the photocatalyst under visible light is significantly improved, the degradation efficiency of toxic organic compounds such as phenol is enhanced, and the problems of rapid charge recombination and poor charge mobility of pure sodium bismuthate photocatalysts are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406440A_ABST
    Figure CN119406440A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material as well as a preparation method and application thereof, and relates to the technical field of photocatalysis. The preparation method comprises the following steps: firstly, preparing nitrogen-doped graphene quantum dots through an ammonium citrate oil bath pyrolysis reaction, and then precipitating the nitrogen-doped graphene quantum dots on flaky sodium bismuthate in situ to prepare the nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material. According to the nitrogen-doped graphene quantum dot / sodium bismuthate composite photocatalytic material prepared by the invention, the defects that photogenerated charges generated by photoexcitation of pure sodium bismuthate are easy to compound, the charge mobility is relatively poor and reaction species are not sufficiently utilized are greatly improved, so that the nitrogen-doped graphene quantum dot / sodium bismuthate composite photocatalytic material can generate higher photocatalytic activity under the action of visible light; the method can be widely applied to degradation of toxic organic pollutants. Meanwhile, the synthesis method provided by the invention has the advantages of simple process, environmental friendliness, low energy consumption, high controllability and the like, and is convenient for large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and in particular to a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material and a preparation method and application thereof. Background Art

[0002] Environmental pollution caused by harmful organic compounds is becoming increasingly serious, and the effective treatment of organic pollutants in the environment has become an important issue of social concern. The current methods used to remove organic pollutants from wastewater include biological, physical and chemical treatments. Among chemical treatments, photocatalysis is considered to be a promising technology because it can mineralize most organic pollutants by using only light energy. Among the reported photocatalysts, TiO2 has become the most widely studied photocatalyst due to its various advantages such as low cost, chemical stability and non-toxicity. However, due to its wide band gap (Eg = 3.0~3.2eV), it cannot effectively utilize visible light, which hinders the effective absorption of sunlight. Appropriate volume and surface modification of TiO2 is beneficial to improve its visible light sensitivity, but the development of new visible light non-TiO2 photocatalysts, such as BiVO4, BiFeO3, and Ag3PO4, has received more attention.

[0003] Bismuth-based oxides are attractive non-TiO2 photocatalysts due to their unique electronic structure and good photoactivity. 3+ The filled Bi6s band and Bi 5+ Bi-based oxides have narrow band gaps, strong visible light absorption, and easily migrated holes. The pentavalent bismuth-based catalyst NaBiO3 has a unique layered structure with a conduction band composed of mixed Na 3s, Bi 6s, and O 2p orbitals, a band gap of about 2.5 eV, and can be excited by visible light. However, fast electron / hole pair recombination, poor charge mobility, and insufficient utilization of reactive species hinder NaBiO3 from having excellent photoactivity. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material to prepare a more effective visible light catalyst.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material, comprising the following steps: The nitrogen-doped graphene quantum dots were firstly prepared by pyrolysis reaction of ammonium citrate in an oil bath, and then the nitrogen-doped graphene quantum dots were in-situ precipitated onto flaky sodium bismuthate to prepare the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material.

[0006] Furthermore, the specific steps of preparing nitrogen-doped graphene quantum dots by ammonium citrate oil bath pyrolysis reaction include: dissolving ammonium citrate in a container filled with water, placing the container in an oil bath pot for heating, taking out and cooling to obtain a black product, dissolving the black product with water and putting it into a dialysis bag, and then placing the dialysis bag into a container filled with water, regularly replacing the water in the container until the water no longer changes color, and then drying the dialyzed product to obtain a black powder, namely nitrogen-doped graphene quantum dots (N-GQDs).

[0007] The heating temperature in the above step can be 200°C, and the heating reaction time can be 30 min. The drying temperature in the above step can be 80°C, and the drying time can be 12 to 24 h. In addition, after the black product is dissolved in water, its pH can be adjusted to 7.

[0008] Furthermore, the specific steps of preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material by in-situ precipitation of nitrogen-doped graphene quantum dots on flaky sodium bismuthate include: first preparing the nitrogen-doped graphene quantum dots and flaky sodium bismuthate into dispersions respectively, then adding the nitrogen-doped graphene quantum dots dispersion into the sodium bismuthate dispersion, stirring the reaction and collecting the precipitate, washing and drying, and obtaining the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material.

[0009] The cleaning operation in the above steps may be performed by centrifugal washing, and the centrifugal washing speed may be 8000 r / min, and the centrifugal time may be 10 to 15 min. The drying temperature in the above steps may be 80° C., and the drying time may be 12 h.

[0010] The step of preparing the nitrogen-doped graphene quantum dot dispersion includes: adding nitrogen-doped graphene quantum dots to water (such as deionized water) and ultrasonically dispersing them for 30 minutes to obtain the nitrogen-doped graphene quantum dot dispersion.

[0011] The step of preparing the sodium bismuthate dispersion includes: adding flaky sodium bismuthate to ethanol (such as anhydrous ethanol) and water (such as deionized water), ultrasonically treating for 30 minutes, and stirring at room temperature for 30 minutes to fully disperse the flaky sodium bismuthate to obtain the sodium bismuthate dispersion.

[0012] Furthermore, the mass percentage of nitrogen-doped graphene quantum dots in the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material is 0.6-1.4%.

[0013] The nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material can be recorded as XN-GQDs / NaBiO3, wherein X is the mass percentage of N-GQDs, and X is 0.6 to 1.4.

[0014] Preferably, the mass percentage of nitrogen-doped graphene quantum dots in the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material is 0.8%, that is, X in XN-GQDs / NaBiO3 is 0.8.

[0015] Furthermore, when the ammonium citrate is dissolved in a container filled with water, the mass ratio of the ammonium citrate to water is 1:(30-50). For example, the mass ratio of the ammonium citrate to water is 1:40, or 1g of ammonium citrate corresponds to 40ml of water.

[0016] Furthermore, the dialysis bag is an MD44 dialysis bag with a specification of molecular weight 1000.

[0017] Furthermore, the particle size of the prepared nitrogen-doped graphene quantum dots is 2 to 5 nm.

[0018] Furthermore, the nitrogen-doped graphene quantum dot dispersion includes nitrogen-doped graphene quantum dots and water, wherein every 3.8 to 8.8 mg of nitrogen-doped graphene quantum dots corresponds to 10 ml of water.

[0019] Furthermore, the sodium bismuthate dispersion includes flaky sodium bismuthate, ethanol (such as anhydrous ethanol) and water, wherein the mass ratio of the flaky sodium bismuthate, ethanol and water is 1: (20-40): (20-40).

[0020] Preferably, every 0.632 g of flaky sodium bismuthate corresponds to 20 ml of ethanol and 20 ml of water.

[0021] Further, every 3.8-8.8 mg of nitrogen-doped graphene quantum dots corresponds to 0.632 g of flaky sodium bismuthate, or the mass ratio of the nitrogen-doped graphene quantum dots to the flaky sodium bismuthate is (3.8-8.8): 632. For example, the nitrogen-doped graphene quantum dots are 3.8-8.8 mg, and the flaky sodium bismuthate is 0.632 g.

[0022] Wherein, the flaky sodium bismuthate may be commercial flaky sodium bismuthate, which may be of analytical grade.

[0023] Wherein, the water involved in the above preparation method can be deionized water.

[0024] Another object of the present invention is to provide a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material, which is prepared by the above-mentioned preparation method.

[0025] In addition, the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material can be applied to degrade phenol solution. Specifically, the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material is dispersed in a solution containing phenol.

[0026] The present invention obtains nitrogen-doped graphene quantum dots by oil bath pyrolysis reaction of ammonium citrate, and then prepares nitrogen-doped graphene quantum dots / sodium bismuthate composite photocatalytic materials by in-situ precipitation of nitrogen-doped graphene quantum dots onto flaky sodium bismuthate. Among them, the present invention uses a single raw material ammonium citrate as a carbon source and a nitrogen source, and prepares nitrogen-doped graphene quantum dots by oil bath pyrolysis reaction, and the preparation process and raw materials are simple. Moreover, the nitrogen-doped graphene quantum dots / sodium bismuthate composite photocatalytic material prepared by the present invention greatly improves the shortcomings of easy recombination of photogenerated charges generated by light excitation of pure sodium bismuthate, poor charge mobility and insufficient utilization of reactive species, so that it produces higher photocatalytic activity under the action of visible light, and can be widely used in the degradation of toxic organic pollutants. At the same time, the synthesis method provided by the present invention has the advantages of simple process, environmental friendliness, low energy consumption and strong controllability, and is convenient for large-scale production and application.

[0027] Moreover, the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material prepared by the present invention has nitrogen-doped graphene quantum dots deposited on the surface of flaky sodium bismuthate, thereby constructing an effective surface separation center, prolonging the carrier lifetime, increasing the reaction sites and accelerating the interfacial redox reaction, so that it has higher visible light catalytic performance, has an excellent degradation effect on phenol, and has broad application prospects in the treatment of harmful organic compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM picture 1 of nitrogen-doped graphene quantum dots (N-GQDs) in Example 1; Figure 2 The second SEM image of nitrogen-doped graphene quantum dots (N-GQDs) in Example 1; Figure 3 XRD patterns of raw material sodium bismuthate and XN-GQDs / NaBiO3 prepared in each embodiment; Figure 4 The SEM image of the raw material sodium bismuthate; Figure 5 This is the SEM image of 0.8 N-GQDs / NaBiO3 prepared in Example 2; Figure 6 Solid UV-visible diffuse reflectance spectra of the raw material sodium bismuthate and 0.8 N-GQDs / NaBiO3 prepared in Example 2; Figure 7 The transient photocurrent response diagram of the raw material sodium bismuthate and 0.8 N-GQDs / NaBiO3 prepared in Example 2; Figure 8 Electrochemical impedance spectroscopy (EIS) diagram of raw material sodium bismuthate and 0.8 N-GQDs / NaBiO3 prepared in Example 2; Fig. 9 The degradation curves of the XN-GQDs / NaBiO3 composite photocatalytic material prepared in each example and pure sodium bismuthate in degrading phenol under visible light irradiation are shown. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.

[0030] The problems of pure NaBiO3 (rapid electron / hole pair recombination, poor charge mobility, and insufficient utilization of reactive species) can be solved by constructing effective surface separation centers to extend carrier lifetime, increase reaction sites, and accelerate interfacial redox reactions. In this regard, ultrasmall nitrogen-doped graphene quantum dots (N-GQDs) can be a promising candidate for integration with NaBiO3 matrix. Compared with large-sized materials with many surface defects as electron-hole recombination centers at the interface, N-GQDs as zero-dimensional (0D) carbon materials can reduce the number of interfacial defects. N-GQDs have been widely studied in the fields of electrochemical biosensors, photovoltaic devices, and energy conversion due to their low cost, limited toxicity, high chemical stability, excellent conductivity, and unique edge and quantum confinement effects. In particular, the upconversion photoluminescence properties make N-GQDs a good photosensitizer for capturing visible and near-infrared light. By utilizing their electron transfer / storage capabilities, N-GQDs can also be used to develop hybrid photocatalysts to accelerate interfacial charge carrier migration, extend charge lifetime, and reduce light-blocking effects.

[0031] Based on this, the present invention constructs a more effective visible light catalyst by attaching N-GQDs on NaBiO3 nanosheets to form a nanoscale heterojunction.

[0032] Based on the above inventive concept, the present invention provides a method for preparing a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material, which specifically comprises the following steps: Step 1: Dissolve amine citrate in a beaker filled with deionized water, place the beaker in an oil bath, heat to 200°C, react for 30 minutes, take out, cool and dissolve the black product in deionized water, adjust its pH to 7, then transfer it to an MD44 dialysis bag and place it in a beaker filled with deionized water. Change the water every once in a while until the water no longer changes color. After dialysis, pour it into a watch glass and dry it in a drying oven at 80°C to obtain a black powder, which is nitrogen-doped graphene quantum dots (N-GQDs).

[0033] Step 2: First, N-GQDs were added to deionized water for ultrasonic dispersion for 30 min to obtain an N-GQDs dispersion; then, commercial flake sodium bismuthate was added to anhydrous ethanol and deionized water for ultrasonic treatment for 30 min, and stirred at room temperature for 30 min to fully disperse it to obtain a sodium bismuthate dispersion; finally, N-GQDs dispersion was added to the sodium bismuthate dispersion, and the precipitate was collected in a centrifuge tube after stirring for 2 h, and washed three times with deionized water by centrifugation. After washing, it was placed in a vacuum drying oven to dry, and a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material was obtained, which was recorded as XN-GQDs / NaBiO3, where X is the mass percentage of N-GQDs, and X is 0.6-1.4.

[0034] Wherein, the mass ratio of ammonium citrate to deionized water in step 1 is 1:(30-50); the specification of the MD44 dialysis bag is a molecular weight of 1000, and the drying time is 12-24 h.

[0035] Wherein, the particle size of the N-GQDs particles in step 1 is 2 to 5 nm.

[0036] Wherein, in step 2, the mass ratio of sodium bismuthate, anhydrous ethanol and deionized water is 1: (20-40): (20-40); the centrifugal washing speed is 8000 r / min, the centrifugal time is 10-15 min, the vacuum drying temperature is 80°C, and the drying time is 12 h.

[0037] Wherein, the commercial flaky sodium bismuthate in step 2 is analytically pure, and X is 0.8. Example 1

[0038] (1) Preparation of nitrogen-doped graphene quantum dots (N-GQDs): Dissolve 1 g of amine citrate in a beaker containing 40 ml of deionized water, place the beaker in an oil bath, heat to 200 °C, react for 30 min, take out, cool and dissolve the black product in deionized water, adjust its pH to 7, then transfer it to an MD44 dialysis bag (molecular weight 1000) and place it in a beaker containing deionized water. Change the water every once in a while until the water no longer changes color. After dialysis, pour it into a watch glass and place it in a drying oven at 80 °C for 24 hours. The obtained black powder is N-GQDs (particle size is 2-5 nm). Figure 1 and Figure 2 .

[0039] (2) Preparation of N-GQDs dispersion and sodium bismuthate dispersion: 3.8 mg of N-GQDs prepared by oil bath pyrolysis method was weighed, and 10 ml of deionized water was added for ultrasonic dispersion for 30 min to obtain N-GQDs dispersion; 0.632 g of commercial flake sodium bismuthate was added to 20 ml of anhydrous ethanol and 20 ml of deionized water, and ultrasonically treated for 30 min, and stirred at room temperature for 30 min to fully disperse it to obtain sodium bismuthate dispersion; (3) Preparation of nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material (X N-GQDs / NaBiO3): N-GQDs dispersion was added to sodium bismuthate dispersion, stirred for 2 h, centrifuged at 8000 r / min for 15 min, and washed three times with deionized water. After washing, it was placed in a vacuum drying oven at 80 °C for 12 h to obtain nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material, recorded as 0.6 N-GQDs / NaBiO3 (the mass percentage of N-GQDs is 0.6%). Example 2

[0040] Except that the mass of N-GQDs was replaced with 5.0 mg, the rest was the same as in Example 1, and a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material was obtained, which was recorded as 0.8 N-GQDs / NaBiO3 (the mass percentage of N-GQDs was 0.8%). Example 3

[0041] Except that the mass of N-GQDs was replaced with 6.3 mg, the rest was the same as in Example 1, and a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material was obtained, which was recorded as 1.0 N-GQDs / NaBiO3 (the mass percentage of N-GQDs was 1.0%). Example 4

[0042] Except that the mass of N-GQDs was replaced with 7.6 mg, the rest was the same as in Example 1, and a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material was obtained, which was recorded as 1.2 N-GQDs / NaBiO3 (the mass percentage of N-GQDs was 1.2%). Example 5

[0043] Except that the mass of N-GQDs was replaced with 8.8 mg, the rest was the same as in Example 1, and a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material was obtained, which was recorded as 1.4 N-GQDs / NaBiO3 (the mass percentage of N-GQDs was 1.4%).

[0044] Characterization of catalysts:

[0045] Powder X-ray diffraction (XRD) was performed on a PANalytical Xpert Pro X-ray diffractometer with Cu K radiation at 40 mA, 40 kV. The morphology of the samples was investigated by scanning electron microscopy (SEM, FEI, Netherlands). Diffuse reflectance spectra (DRS) were recorded on a Shimadzu UV-2700 spectrophotometer with BaSO4 as reference. Transient photocurrent response and electrochemical impedance spectroscopy were measured by an electrochemical workstation (CHI-750E).

[0046] Catalyst degradation performance test:

[0047] 25 mg of photocatalyst was dispersed in 100 mL of phenol (20 mg·L -1 ) solution. Before light irradiation, magnetic stirring was continued for 30 min in the dark to reach adsorption-desorption equilibrium. The mixture was then irradiated with a 300 W xenon lamp combined with a 420 nm cutoff filter. At certain time intervals, 3 mL of the mixture was centrifuged and filtered, and finally, the filtrate concentration was analyzed using a Shimadzu UV-2700 UV-visible spectrophotometer.

[0048] Specific instructions:

[0049] Figure 3 XRD patterns of raw material NaBiO3 and product XN-GQDs / NaBiO3 prepared in Examples 1 to 5. It can be seen that they all have strong diffraction peaks, indicating that they all have good crystallinity. Further analysis shows that the raw material NaBiO3 is a rhombohedral crystal system, and most of the peaks correspond to NaBiO3 . 2H2O (JCPDS. No.30-1160), the XRD pattern of product X N-GQDs / NaBiO3 is almost consistent with that of raw material NaBiO3, and there is no obvious characteristic peak of N-GQDs, which is attributed to the small amount of N-GQDs added and its significant scattering.

[0050] Figure 4 and Figure 5 SEM images of the raw material NaBiO3 and the product 0.8 N-GQDs / NaBiO3 prepared in Example 2. Figure 4 It was found that the raw material NaBiO3 is mainly in the shape of flake flower clusters, while the morphology of 0.8 N-GQDs / NaBiO3 ( Figure 5 ) is similar to the raw material NaBiO3.

[0051] Figure 6The solid UV-visible diffuse reflectance spectra of the raw material sodium bismuthate and 0.8 N-GQDs / NaBiO3 prepared in Example 2. It is found that the absorption band edge of NaBiO3 is about 500 nm, while the absorption band edge of 0.8 N-GQDs / NaBiO3 obtained by attaching N-GQDs to the flaky NaBiO3 is about 510 nm, which is slightly red-shifted, which is attributed to the up-conversion photoluminescence characteristics of N-GQD.

[0052] Figure 7 and Figure 8 The transient photocurrent response diagram of the raw material sodium bismuthate and 0.8 N-GQDs / NaBiO3 prepared in Example 2 ( Figure 7 ) and electrochemical impedance spectroscopy (EIS) graphs ( Figure 8 ). Photocurrent response and electrochemical impedance spectroscopy (EIS) can analyze the carrier separation and recombination of photocatalysts. Figure 7 As shown in the figure, the photocurrent response intensity of the 0.8 N-GQDs / NaBiO3 composite photocatalyst is more than twice that of NaBiO3, which is attributed to the fact that photogenerated electrons can be quickly transferred through N-GQDs, thereby improving the carrier separation efficiency. Figure 8 As shown in the figure, compared with NaBiO3, the 0.8 N-GQDs / NaBiO3 composite photocatalyst has a smaller arc radius, which also proves that its carriers can be separated more effectively. These results show that the carrier separation efficiency of NaBiO3 can be significantly improved by compounding with NGQDs, thereby improving its photocatalytic activity.

[0053] Fig. 9 The degradation curves of XN-GQDs / NaBiO3 composite photocatalyst prepared in different embodiments and pure sodium bismuthate for degradation of phenol under visible light irradiation are shown. It can be seen that under visible light irradiation, the degradation rate of phenol by raw material NaBiO3 reaches 91.7% in 50 min, and the degradation rate of phenol by XN-GQDs / NaBiO3 composite photocatalyst prepared in different embodiments is faster than that of raw material NaBiO3. As the content of N-GQDs increases from 0.6% to 1.4%, the degradation rate of phenol increases first and then decreases. Among them, the degradation rate of phenol by 0.8N-GQDs / NaBiO3 composite photocatalyst is the fastest, and the degradation rate of phenol reaches 92.6% after 30 min of visible light irradiation.

[0054] The embodiments described above are only some embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Any changes and improvements made to the principles, process conditions (such as the amount of catalyst, solution concentration, etc.) and applications (such as degradation of dyes, antibiotics and other organic toxic wastewater) of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material, characterized in that: The following steps are involved: The nitrogen-doped graphene quantum dots were firstly prepared by pyrolysis reaction of ammonium citrate in an oil bath, and then the nitrogen-doped graphene quantum dots were in-situ precipitated onto flaky sodium bismuthate to prepare the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material.

2. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 1, characterized in that: The specific steps of preparing nitrogen-doped graphene quantum dots by ammonium citrate oil bath pyrolysis reaction include: Dissolve ammonium citrate in a container filled with water, then place the container in an oil bath to heat it, take it out and cool it to obtain a black product, dissolve the black product with water and put it into a dialysis bag, then put the dialysis bag into a container filled with water, regularly change the water in the container until the water no longer changes color, and then dry the dialyzed product to obtain a black powder, which is nitrogen-doped graphene quantum dots.

3. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 1, characterized in that: The specific steps of preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material by in-situ precipitation of nitrogen-doped graphene quantum dots onto flaky sodium bismuthate include: First, nitrogen-doped graphene quantum dots and flaky sodium bismuthate are prepared into dispersions respectively, and then the nitrogen-doped graphene quantum dot dispersion is added into the sodium bismuthate dispersion. After stirring for reaction, the precipitate is collected, washed and dried to obtain a nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material.

4. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 1, characterized in that: The mass percentage of nitrogen-doped graphene quantum dots in the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material is 0.6-1.4%.

5. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 2, characterized in that: When the ammonium citrate is dissolved in a container filled with water, the mass ratio of the ammonium citrate to water is 1:(30-50).

6. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 3, characterized in that: The sodium bismuthate dispersion includes flaky sodium bismuthate, ethanol and water, and the mass ratio of the flaky sodium bismuthate, ethanol and water is 1: (20-40): (20-40).

7. The method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 1 or 3, characterized in that: Every 3.8 to 8.8 mg of nitrogen-doped graphene quantum dots corresponds to 0.632 g of flaky sodium bismuthate.

8. A nitrogen-doped graphene quantum dot / sodium bismuthate photocatalytic composite material, characterized in that: The photocatalytic composite material is prepared by the method for preparing the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to any one of claims 1 to 7.

9. Use of the nitrogen-doped graphene quantum dots / sodium bismuthate photocatalytic composite material according to claim 8 in degrading phenol solution.

Citation Information

Patent Citations

  • Active carbon fiber-loaded NaBiO3-based composite oxide and preparation method thereof, and method for degrading organic dye waste water by using composite oxide

    CN103623805A

  • Synthesis and application of nitrogen-doped graphene quantum dot / similar-graphene phase carbon nitride composite material

    CN105289689A

  • Method for preparing heterojunction photocatalyst

    CN106311307A

  • Method for improving catalytic effect of NaBiO3 visible light based on metal nano particles

    CN108176391A

  • Preparation method of activated carbon fiber loaded sodium bismuthate adsorption catalysis material

    CN108940196A